DBS and SMU join hands to launch sustainability programme - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
Singapore Management University (SMU) and DBS have established a partnership on a comprehensive initiative – the first-of-its-kind in Southeast Asia – that focuses on promoting and growing sustainability. The wide-ranging initiative includes the introduction of Singapore’s first sustainability major, as well as funding for sustainability research, scholarships, fellowships and community engagement. The DBS-SMU Sustainability Initiative, which the bank plans to commit more than SGD one million towards aims to provide further support to academics, businesses and students passionate about tackling real world sustainability challenges.For the first time, the SMU Lee Kong Chian School of Business will be offering a major in sustainability in Academic Year 2019. The major aims to develop graduates who will be equipped with the knowledge and skills to implement sustainable practices in businesses that lead to long-term, measurable impact.